2021
DOI: 10.1002/ajh.26119
|View full text |Cite
|
Sign up to set email alerts
|

Single‐agent cladribine as an effective front‐line therapy for adults with Langerhans cell histiocytosis

Abstract: ID number selected at random. In addition, we will strongly recommend that all recipient groups ensure that every member of the staff sign a Confidentiality Agreement. We will develop a data and resource sharing agreement with the legal advice from the Compliance Office of the University of Alabama at Birmingham, and ensure that we follow NIH guidelines with respect to data sharing. Before data are shared with researchers, we will require that researchers enter into a data-sharing and resource-sharing agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
1
19
0
4
Order By: Relevance
“…cytotoxic chemotherapy, corticosteroids, immunosuppression and/or interferon-alpha), ALK inhibition, or a combination of these. As previously published for Erdheim-Chester disease (ECD) and Langerhans cell histiocytosis (LCH) 27,52,53 , responses to treatment as documented in the medical record were classified as complete response (complete resolution of disease), partial response (partial resolution of disease), stable disease (no significant change in lesions), or progressive disease (growth of known lesions or appearance of new lesions). Responses were extracted from the clinical medical records and based on formal clinical interpretations of ultrasound, computed tomography (CT), magnetic resonance imaging (MRI) and/or positron emission tomography (PET)-CT when available.…”
Section: Clinical and Radiologic Assessment And Data Collectionmentioning
confidence: 99%
“…cytotoxic chemotherapy, corticosteroids, immunosuppression and/or interferon-alpha), ALK inhibition, or a combination of these. As previously published for Erdheim-Chester disease (ECD) and Langerhans cell histiocytosis (LCH) 27,52,53 , responses to treatment as documented in the medical record were classified as complete response (complete resolution of disease), partial response (partial resolution of disease), stable disease (no significant change in lesions), or progressive disease (growth of known lesions or appearance of new lesions). Responses were extracted from the clinical medical records and based on formal clinical interpretations of ultrasound, computed tomography (CT), magnetic resonance imaging (MRI) and/or positron emission tomography (PET)-CT when available.…”
Section: Clinical and Radiologic Assessment And Data Collectionmentioning
confidence: 99%
“…Purine-analog chemotherapies cytarabine and cladribine given as monotherapies are effective for neurologic LCH; some specialists use these agents as first-line therapy while others reserve them for relapsed or refractory disease. 27 , 36 , 37 The implications of BRAF and other MAPK pathway mutational status upon LCH treatment remain largely unclear. BRAF or MEK inhibitors have demonstrated efficacy in prospective trials of histiocytosis patients, although with a small proportion of LCH participants.…”
Section: Langerhans Cell Histiocytosismentioning
confidence: 99%
“…63 A more recent retrospective study conducted at an NCCN Member Institution also showed a high ORR (79%) in adults with multifocal LCH (n=38; 82% multisystem) who were treated with cladribine, with complete response (CR) and partial response (PR) observed in 26% and 53% of patients, respectively. 64 Fiveyear overall survival (OS), progression-free survival (PFS), and duration of response (DOR) for the sample was 75%, 58%, and 70%, respectively. There is also evidence supporting clofarabine for relapsed/refractory LCH in the pediatric setting, with disease improvement observed in 73% of 11 patients.…”
Section: Tissue Biopsy Cbc Abnormalitymentioning
confidence: 99%